A dynamic nonlinear model used for controller design of a 600 MW supercritical circulating fluidized bed boiler-turbine unit - Zhang, Hongfu; Gao, Mingming; Yu, Haoyang; Fan, Haohao; Zhang, Jiahui (Applied thermal engineering, 2022)
•Energy storage characteristic and variable coal quality are considered in modeling.•Parameters in model change with different load condition to improve model accuracy.•The model is validated by a 600 MW supercritical once-through CFB unit.•Open-loop step responses show the different inertia and nonlinearity of CCS.•Transfer function matrix of CCS is derived from the dynamic nonlinear model. Large-scale circulating fluidized bed (CFB) power generation units with high steam pressure and temperature have been put into operation in order to obtain high cycle efficiency and less emissions. To ensure the flexible operation of such CFB units, it is necessary to build a model for the design of coordinated control system (CCS). However, few studies focus on modeling of such CFB units. Thus, this work develops a mechanistic dynamic nonlinear model of a large-scale supercritical CFB unit, which is suitable for CCS design because of its relatively low complexity. Firstly, model structure is derived from mass and energy conservation laws, combined with analysis of operational characteristics of a 600 MW supercritical CFB unit. Then, unknown parameters and nonlinear functions in model are identified based on running data by using regression analysis and optimization algorithm. Validation results show that the model has satisfactory accuracy and it can capture essential dynamic characteristics of the unit and nonlinearity of CCS. More importantly, the model accuracy is further improved by proposed variable dynamic parameters and correction of coal quality. After this, transfer function matrix of CCS is derived from dynamic nonlinear model, which can be applied to controller design and simulation analysis.